2000
DOI: 10.1177/204748730000700509
|View full text |Cite
|
Sign up to set email alerts
|

Social Gradients in Cardiovascular Risk Factors and Symptoms of Swedish Men and Women: The Göteborg MONICA Study 1995

Abstract: Background Even though coronary mortality in middle and old age is decreasing, social gradients may be increasing; but they need not necessarily be the same for men and women. In order to develop efficient preventive strategies more knowledge of the current distributions of risk factors both for men and for women is needed. Objective To investigate and to compare the socio-economic gradients for coronary risk factors of men and women. Design A cross-sectional study. Methods We studied 686 men and 825 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
(46 reference statements)
8
21
0
4
Order By: Relevance
“…This study also confirms that high education is associated with lower levels of some cardiovascular risk factors [5]. We have shown significant differences for many of the risk factors between the two educational groups, with similar patterns in both sexes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study also confirms that high education is associated with lower levels of some cardiovascular risk factors [5]. We have shown significant differences for many of the risk factors between the two educational groups, with similar patterns in both sexes.…”
Section: Discussionsupporting
confidence: 85%
“…Even in a country like Sweden with a relatively narrow income distribution, there are health differences between social groups [2][3][4][5]. Social inequalities in self-reported health have actually been reported to be larger in Sweden compared to some other European countries [6] and inequalities in the risk of coronary heart disease seems to be greater in northern European countries compared with southern Europe [7].…”
Section: Introductionmentioning
confidence: 99%
“…12,53 Similar analogous findings are noted in cardiovascular studies where low SES exerts a stronger adverse influence on cardiovascular risk factors of women than it does on those of men 54,55 and in diabetic studies where a negative association between SES and prevalence of diabetes was found only among women. 49,56 Not all studies have consistently shown these gender patterns.…”
Section: Ethical Issuessupporting
confidence: 69%
“…25,26 Whereas a consistent association between high lipid levels and lower socio-economic conditions has been found in women, 23,27-29 the relationship in men has been less consistent. 23,[27][28][29] Using data from the MRC National Survey of Health and Development (NSHD), we study the association between birth weight and lipids in a sample of 53-year-old British men and women followed-up since their birth in 1946. The sample is large enough to allow us to formally test for sex differences in the relationship between birth weight and lipid levels.…”
mentioning
confidence: 99%